The potential of chitosan combined with chicken shank collagen as scaffold on bone defect regeneration process in Rattus norvegicus - Fitria Rahmitasari; Retno Pudji Rahayu; Elly Munadziroh (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: In the field of dentistry, alveolar bone damage can be caused by periodontal disease, traumatic injury due to tooth extraction, cyst enucleation, and tumor surgery. One of the ways to regenerate the bone defect is using graft scaffold. Thus, combination of chitosan and collagen can stimulate osteogenesis. Purpose: The aim of this study was to examine the potential of chitosan combined with chicken shank collagen on bone defect regeneration process. Method: Twelve Rattus norvegicus were prepared as animal models in this research. A bone defect was intentionally created at both of the right and left femoral bones of the models. Next, 24 samples were divided into four groups, namely Group 1 using chitosan – collagen scaffold (50:50), Group 2 using chitosan collagen-scaffold (80:20), Group 3 using chitosan scaffold only, and Control Group using 3% CMC-Na. On 14th day, those animals were sacrificed, and histopathological anatomy examination was conducted to observe osteoclast cells. In addition, immunohistochemistry examination was also performed to observe RANKL expressions. Result: There was a significant difference in RANKL expressions among the groups, except between Group 3 using chitosan scaffold only and control group (p value > 0.05). The highest expression of RANKL was found in Group 1 with chitosan – collagen scaffold (50:50), followed by Group 2 with chitosan-collagen scaffold (80:20). Moreover, there was also a significant difference in osteoclast generation, except between Group 1 using chitosan – collagen scaffold (50:50) and Group 2 using chitosan-collagen scaffold (80:20), p value < 0.05; and between Group 3 using chitosan scaffold only and control group, p value > 0.05. Less osteoclast was found in the groups using chitosan – collagen scaffold (Group 1 and Group 2). Conclusion: Combination of chitosan and chicken shank collagen scaffold can improve regeneration process of bone defect in Rattus novergicus animals through increasing of RANKL expressions, and decreasing of osteoclast.